TIPOLOGI KLASSEN PEREKONOMIAN DI KABUPATEN KUBU RAYA PERIODE 2008 – 2011 - B01108041, RICHI RIYANTO (Jurnal Pembangunan dan Pemerataan, 2014)
This study aims to map and analyze the performance of the district / city in West Kalimantan, especially to see the Kubu Raya District, as well as investigate and analyze the performance of the economic sectors in Kubu Raya district. This study used a descriptive method, the research that describes the circumstances and events based on facts and data are available and relevant to the study variables. The data used are secondary data are time series (time series) of data that is Gross Domestic Product (GDP) and Kubu Raya district of West Kalimantan in 2008 until 2011 This study used a model Quotients Klassen is useful to know-sector leading sector and the potential to be developed in Kubu Raya district. Based on the results of the analysis method Klassen Typology Based on GDP per capita in West Kalimantan using two components of economic income and economic growth rate of Kubu Raya district occupies an area within the category as fast forward and fast-growing, while the results of the analysis method Klassen Typology Based on Constant Market Prices GDP in order to see economic sectors Kubu Raya District uses two components, namely the rate of economic growth and the contribution of economic sectors Kubu Raya District apparently has not had a prime sector.